‘Stand up if you love football!’ Methods of Creating Dynamics and Pace of Gameplay in Animated Television Series for Children Focused on Football - Stasieńko, Jan; Ostrowski, Andrzej (INSTED: Interdisciplinary Studies in Education & Society, 2024)
Animated television series about soccer/football are a grateful area of research on the visual layer because these are productions located at the intersection of the specificity of film work for children, animation techniques used by the creators themselves, historical and cultural factors influencing their final aesthetics and the conditions of the soccer as a sports discipline. This article aims to indicate the ways of reflecting the dynamics of the sports events in the animated series selected for the analysis. The idea of the text is to answer the question of to what extent the dynamics of soccer/football events presented in television cartoons are a representation of the pace and drama of real sports events and imitation of the accompanying television broadcasts, and to what extent it is the creation of a new visual drama based on specific and unique effects and means of expression.